PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Yulianatasya, Salsabila Aurelyta; Manunggal, Syafrudin Arif Marah (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The development of Industry 5.0 is currently experiencing progress and development in various sectors. In the face of free competition, every corporation must own and implement a new strategy or method of competing. The banking sector is one industry that significantly affects the economy. The banking sector has a significant impact on a region's or nation's economic growth. Whether the economy is strong or weak, banking companies will be heavily impacted. This study aims to determine the effect of Intellectual Capital on firm value with financial performance as an intervening variable. This research was conducted at banking companies listed on the Indonesia Stock Exchange in 2018 – 2021. The sample selection method used was purposive sampling, so that 19 observational samples were obtained. Data analysis used in the form of panel data regression techniques and Chow test. The results showed that Intellectual Capital has an effect on firm value, Intellectual Capital has an effect on financial performance, Financial performance has an effect on firm value, Financial performance mediates the relationship between intellectual capital on firm value.